Analisis Pemanfaatan Pelayanan Rawat Jalan Peserta JKN Dengan Diagnosa Tuberculosis Paru di DKI Jakarta Tahun 2019 : Analisis Data Sampel BPJS Kesehatan Tahun 2022 - Reza Rahman; Budi Hidayat (Syntax Idea)
The number of cases of pulmonary tuberculosis based on data from the Central Statistics Agency in DKI Jakarta in 2020-2021 has increased. Pulmonary tuberculosis is an infectious disease that currently causes a high mortality rate. In the implementation of National Health Insurance (JKN), pulmonary tuberculosis is a type of disease that is guaranteed and can be treated with FKTP services. This study uses BPJS Health tertiary data with Poisson regression modeling and Negative Binomial regression which aims to determine the description of visits by JKN participant tuberculosis sufferers to outpatient services in DKI Jakarta. The subjects of the research were all patients diagnosed with pulmonary TB who were undergoing outpatient treatment based on BPJS Health contextual tuberculosis sample data. The results of this study showed that there were 625 participants diagnosed with pulmonary TB, the majority of whom were male, in the adult age category, and in the Contribution Assistance Recipient (PBI) segment. From the modeling carried out, it was found that 8 (eight) variables significantly influenced the utilization of outpatient health services in DKI Jakarta with the age variable in the elderly group (>55 years) being most dominantly related to the utilization of outpatient services. Service flow as well as promotive and preventive efforts in the target population involving cross-sectors play an important role in treating pulmonary tuberculosis. Based on the description above, research was conducted with the aim of finding out what factors influence the utilization of health services for tuberculosis sufferers of JKN participants in DKI Jakarta.